Effect of chronic low body temperature on feeding and gut passage in a plethodontid salamander. (October 2017) - Marvin, Glenn A.; Bryan, Richard; Hardwick, James
Abstract: Although feeding in some plethodontid salamander species, such as Dusky Salamanders ( Desmognathus, family Plethodontidae), occurs at short-term (acute) low temperature below 5 °C, it is unknown whether feeding, digestion, and gut passage continue to occur during periods of long-term (chronic) low temperature. We performed a controlled laboratory experiment to examine the effect of several chronic low environmental temperatures on both feeding and gut passage in semiaquatic Spotted Dusky Salamanders ( D. conanti ). We quantified salamander feeding and defecation for different experimental groups maintained for many weeks at a constant temperature of 4, 7, 10, or 13 °C. Although feeding frequency, number of prey items consumed per feeding, and defecation frequency were significantly less for individuals at 4 °C than for individuals at 10 or 13 °C, salamanders continued to feed, defecate, and maintain body mass for 12 weeks at 4 °C. The ratio of the number of fecal pellets produced to the number of prey items consumed each week by individuals did not significantly decrease at 4 °C, which indicates gut passage was sustained at this temperature. Because both time between feeding and time between defecation were similarly affected by prolonged low temperature, the significant decrease in feeding frequency at 4 °C may depend, in part, on a decrease in digestive function and an extended time for gut passage at low temperature. We conclude that most individuals of D. conanti can feed, digest, and maintain body mass for several months at constant low temperature down to 4 °C. Our results support a growing body of data that indicate some plethodontid salamanders may acquire energy at environmental temperatures only a few degrees above freezing. Highlights: Prolonged (chronic) low body temperature (Tb ) limits energy intake in many ectotherms. Effect of chronic Tb < 5 °C on digestive ability in plethodontid salamanders is unknown. Effects of chronic low Tb on feeding and gut passage were quantified at 4, 7, 10 and 13 °C. Feeding and gut passage were reduced but yet continued at constant 4 °C for 12 weeks. Salamanders can feed, digest, and maintain body mass at 4 °C for several months.